A nature-based perspective for the Netherlands in 2120 - van Buuren , Michaël (Journal of Delta Urbanism, 2022)
This article elaborates on the method of “research through design” in spatial and landscape design. It includes a further explanation of the method in which three questions are central. At first theoretical backgrounds of research through design are highlighted: what is it? It is stated that he sequence of deduction and induction connected by making creative leaps are the most crucial elements. Second, the added value of the method is stressed. It maybe the only way to contribute to complex or ‘wicked problems’ that characterize present development of landscapes. Finally a working method for the use of research (through) design is proposed. The project “A nature-based perspective for the Netherlands in 2120” illustrates a potential outcome of this way of thinking and working.